Microbial Cellulose Production from Bacteria Isolated from Rotten Fruit - B. E. Rangaswamy; K. P. Vanitha; Basavaraj S. Hungund (International Journal of Polymer Science)
Microbial cellulose, an exopolysaccharide produced by bacteria, has unique structural and mechanical properties and is highly pure compared to plant cellulose. Present study represents isolation, identification, and screening of cellulose producing bacteria and further process optimization. Isolation of thirty cellulose producers was carried out from natural sources like rotten fruits and rotten vegetables. The bacterial isolates obtained from rotten pomegranate, rotten sweet potato, and rotten potato were identified as Gluconacetobacter sp. RV28, Enterobacter sp. RV11, and Pseudomonas sp. RV14 through morphological and biochemical analysis. Optimization studies were conducted for process parameters like inoculum density, temperature, pH, agitation, and carbon and nitrogen sources using Gluconacetobacter sp. RV28. The strain produced 4.7 g/L of cellulose at optimum growth conditions of temperature (30°C), pH (6.0), sucrose (2%), peptone (0.5%), and inoculum density (5%). Characterization of microbial cellulose was done by scanning electron microscopy (SEM).